Effects on the financial statements of the implementation of environmental management in the upper limited industrial rice mill (GEON Journal (Management, Organizations and Business), 2016)
Superior Rice Mill Industry LTDA, has created the Department of Environmental Management DGA to direct environmental management as required by the 1124 Act of 2007 and Decree 1299 of 2008, which allows ensuring compliance with environmental regulations; prevent, minimize and control the generation of pollutant loads to the environment. This issue generates the company to a number of adverse situations that affect their organizational development and can also acarrearle possible sanctions for non-compliance. Therefore, the study aims to determine the effects on the financial statements could be taken for the implementation of environmental management in the company. Methodology. Descriptive research was used, with which the data collected through surveys, books and documents related to the subject was reviewed. Results. 80% of respondents say there is default in environmental laws, as required by the creation of the DGA and the implementation of environmental management system; and 60% say that this is due to lack of staff training and the development of governance to mitigate the negative effects for the environment, for the activities. Conclusions. The company does not perform a process of environmental management through a specialized department as required by law; and that the project implementation, it was concluded that brings effects for business growth.
Keywords: Enviromental management; Enviromental management departament; effects; prevention; implementation; minimization; regulations; environment